Circadian disruption during fetal development promotes pathological cardiac remodeling in male mice - Yang Yu; Jing-Yu Liu; Hui-Jiao Yang; Xiao-Qin Luo; Xiao-Ping Gao; Xiao-Xin Huang; Ao-Xue Tang; Hai-Ying Mary Cheng; Wei-Chao Liu; Peng Zhang (iScience, 2024)
Summary: Disruption of circadian rhythms during fetal development may predispose mice to developing heart disease later in life. Here, we report that male, but not female, mice that had experienced chronic circadian disturbance (CCD) in utero were more susceptible to pathological cardiac remodeling compared with mice that had developed under normal intrauterine conditions. CCD-treated males showed ventricular chamber dilatation, enhanced myocardial fibrosis, decreased contractility, higher rates of induced tachyarrhythmia, and elevated expression of biomarkers for heart failure and myocardial remodeling. In utero CCD exposure also triggered sex-dependent changes in cardiac gene expression, including upregulation of the secretoglobin gene, Scgb1a1, in males. Importantly, cardiac overexpression of Scgb1a1 was sufficient to induce myocardial hypertrophy in otherwise naive male mice. Our findings reveal that in utero CCD exposure predisposes male mice to pathological remodeling of the heart later in life, likely as a consequence of SCGB1A1 upregulation.